PURWARUPA SISTEM PEMANTAUAN POLUSI UDARA DI RUANG TERTUTUP MENGGUNAKAN PLATFORM THINGSPEAK - Kemahyanto Exaudi; Nabillah Selva Setiawan; Aditya P P Prasetyo; Rossi Passarella; Huda Ubaya; Purwita Sari; Rido Zulfahmi; Roswitha Yemima Tiur Mediswati (P3M Politeknik Negeri Indramayu, 2023)
Smoking is an act of negligence that a person commits intentionally and causes personal harm. The habit of smoking has spread to children and adolescents. One of the health impacts of smoking is the smoke that is released. Therefore, cigarette smoke is categorized as one of the causes of air pollution. A bad habit that smokers do is smoking in a closed room with minimal ventilation. As a result, the air in the room is contaminated by harmful substances from cigarette smoke. This study aims to monitor the quality of air exposed to cigarette smoke in a prototype closed room and measure the effectiveness of sansevieria plants placed in the room to absorb cigarette smoke in real-time. Air quality is displayed in graphical form using the Thingspeak Platform. The stages carried out in this research are air quality detected using an MQ-7 sensor integrated with the MCU8266 WiFi Node, converting sensor data into smoke density values in units of PPM (parts per million), displaying air PPM graphs in real-time and displaying the absorption ability of sansevieria against air contaminated with cigarette smoke. The results prove that one pot of sansevieria plants (5 leaves) placed in a prototype room with a size of 70cm x 30cm x 45cm can absorb cigarette smoke within 1 hour 39 minutes. While for two pots of sansevieria plants (10 leaves), it takes 1 hour and 11 minutes. Visualization of the absorption graph and normalization of air in the room can also be monitored in real-time through the Thingspeak platform based on the smoke density value against time.